SCIENTIFIC OBJECTIVITY AND RATIONALITY IN THESIS: THE PEDAGOGICAL ASPECT - V. M. Anikin; B. M. Poizner; E. A. Sosnin (Высшее образование в России)
Intra-scientific and sociocultural factors that act today in the world and inRussiarequire to increase the methodological potential of postgraduate students. To solve this problem the authors propose to focus the attention of a student on the problem of correct expression of new knowledge received by himself. The authors have tested this pedagogical strategy on teaching postgraduate students to formulate defended statements in a thesis. The authors define a certain minimum of concepts and suggest to apply their approach to creativity process. The paper gives the educational topics examples with appropriate bibliography. The student (master's degree and postgraduate) who has already learned this training material is able to qualify his activity (including in the context of the "life cycle" of the scientific or engineering area) and the type of relationship with the research supervisor more objectively. This will also permits him to assess his own potential leadership position in the creative team more realistically.